2016
DOI: 10.1158/1055-9965.epi-15-1246
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Intervention Raises Latina Participation in Mammography Screening: Findings from ¡Fortaleza Latina!

Abstract: Background Breast cancer is the most commonly diagnosed cancer in women in the United States, and Latinas have relatively low rates of screening participation. The Multi-level Intervention to Increase Latina Participation in Mammography Screening study (¡Fortaleza Latina!) sought to assess the efficacy of a clinic- and patient-level program to increase breast cancer screening among Latinas in Western Washington who seek care at a safety net health center. Methods The study enrolled 536 Latinas ages 42-74 who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Using the inclusion criteria for this review, seven studies were initially identified; however, after full text review, two of these studies were removed because the samples did not include over 50% Hispanic participants or did not report results separately for Hispanic women, leaving a final sample of five studies [6,9,10,16,24]. Three studies employed experimental designs with random samples, and two studies used quasi-experimental designs, randomized by study site ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the inclusion criteria for this review, seven studies were initially identified; however, after full text review, two of these studies were removed because the samples did not include over 50% Hispanic participants or did not report results separately for Hispanic women, leaving a final sample of five studies [6,9,10,16,24]. Three studies employed experimental designs with random samples, and two studies used quasi-experimental designs, randomized by study site ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…To calculate ORs for each study, 12-month follow-up periods were used for three studies [6,9,24]. For the Jandorf et al study, the 8-month follow-up period data were used, and for the Fernandez et al study, 6-month follow-up period data were used [10,16].…”
Section: Resultsmentioning
confidence: 99%
“… 34 These items were tested iteratively, modified with the guidance of cultural and survey experts, and cognitively tested in UWOCASO women. 35 The final Attitudes on Breast Cancer Surveillance and Knowledge survey was translated from English (primary language) to Luganda (common local language).…”
Section: Methodsmentioning
confidence: 99%
“… 3 Nevertheless, interventions to increase mammogram utilization in Hispanic women have generally focused on increasing breast cancer screening knowledge, self-efficacy, or decreased real or perceived barriers to screening. 9 12 There continues to be a limited amount of information on what type of knowledge acquired through breast cancer screening interventions is important to affect behavioral change. 4 , 13 , 14 This is despite the consensus that having the correct screening knowledge on breast cancer risk is essential to making informed decisions to be screened.…”
Section: Introductionmentioning
confidence: 99%